Indication for cataract surgery. Do we have evidence of who will benefit from surgery? A systematic review and meta‐analysis. (3rd June 2015) - Kessel, Line; Andresen, Jens; Erngaard, Ditte; Flesner, Per; Tendal, Britta; Hjortdal, Jesper
Abstract: The need for cataract surgery is expected to rise dramatically in the future due to the increasing proportion of elderly citizens and increasing demands for optimum visual function. The aim of this study was to provide an evidence‐based recommendation for the indication of cataract surgery based on which group of patients are most likely to benefit from surgery. A systematic literature search was performed in the MEDLINE, CINAHL, EMBASE and COCHRANE LIBRARY databases. Studies evaluating the outcome after cataract surgery according to preoperative visual acuity and visual complaints were included in a meta‐analysis. We identified eight observational studies comparing outcome after cataract surgery in patients with poor (<20/40) and fair (>20/40) preoperative visual acuity. We could not find any studies that compared outcome after cataract surgery in patients with few or many preoperative visual complaints. A meta‐analysis showed that the outcome of cataract surgery, evaluated as objective and subjective visual improvement, was independent on preoperative visual acuity. There is a lack of scientific evidence to guide the clinician in deciding which patients are most likely to benefit from surgery. To overcome this shortage of evidence, many systems have been developed internationally to prioritize patients on waiting lists for cataract surgery, but the Swedish NIKE (Nationell Indikationsmodell för Katarakt Ekstraktion) is the only system where an association to the preoperative scoring of a patient has been related to outcome of cataract surgery. We advise that clinicians are inspired by the NIKE system when they decide which patients to operate to ensure that surgery is only offered to patients who are expected to benefit from cataract surgery.